2018
DOI: 10.1007/s40520-018-0985-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical delay is a risk factor of delirium in hip fracture patients with mild–moderate cognitive impairment

Abstract: The study supports the concept that older adults with HF should undergo surgery quickly. Patients with mild-to-moderate cognitive impairment should be primarily considered as the best target for interventions aiming to reduce time to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
2
25
0
1
Order By: Relevance
“…In anesthetic and operative risk factors, we found that regional anesthesia is a potential risk factor for POD. However, we also found that the effect of general anesthesia on POD is significant after excluding Chrispal et al 14 and Pioli et al 41 to resolve heterogeneity. In fact, the contribution of the anesthetic method on POD was conflicting.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…In anesthetic and operative risk factors, we found that regional anesthesia is a potential risk factor for POD. However, we also found that the effect of general anesthesia on POD is significant after excluding Chrispal et al 14 and Pioli et al 41 to resolve heterogeneity. In fact, the contribution of the anesthetic method on POD was conflicting.…”
Section: Discussionmentioning
confidence: 45%
“…In this meta-analysis, we divided risk factors for POD into individual as well as anesthetic and operative factors, and detected that individual factors, including advanced age, male, ASA score≥III, lower BMI, smoking, function dependency, visual impairment, preoperative delirium, dementia, hypertension, and COPD, as well as anesthetic and operative factors, including regional anesthesia, transfusion, and elective surgery could promote the development of POD in adult patients after hip fracture surgery. Compared with previous published meta-analysis, 6,7 we add the latest clinical trials data 3,4,13,17,20,22,23,[27][28][29]34,37,38,41,43,50,51,53 and provided updated evidences for clinician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same applies to delirium. Many factors could contribute to the occurrence of postoperative delirium [42,47], including ambulatory status [8,28]. As a result, it is challenging to determine the effect of factors that contribute to the development of pressure sores and delirium.…”
Section: Medical Complicationsmentioning
confidence: 99%
“…The results of this study showed that the delirium group had a longer injury-to-surgery time than the nondelirium group. Pioli et al 18 considered the delay of surgery to be a risk factor for delirium. For older adult hip fracture patients with mild to moderate cognitive impairment, early surgery should be one of the preoperative goals.…”
Section: Discussionmentioning
confidence: 99%